Elimination of mother- to - child transmission of HIV in South Africa : Rapid scale- up using quality improvement - Bardwaj, S.; Barron, P.; Treger-Slavin, P.; et al (My University, 2014)
Background: South Africa (SA) is committed to achieving the goal of eliminating mother-to-child transmission (MTCT) of HIV by 2015. To achieve this, universal coverage of quality antenatal, labour, delivery and postnatal services for all women has to be attained. Over the past decade, the prevention of mother-to-child transmission (PMTCT) programme has been scaled up to reach all healthcare facilities in the country. However, challenges persist in achieving 100% coverage and access to the programme. Objectives: We describe the process undertaken by the National Department of Health (NDoH), in collaboration with partners, to develop, implement and monitor a data-driven intervention to improve facility, district, provincial and national PMTCT-related performance. Methods: Between 2011 and 2013, the NDoH developed and implemented an intervention using data-driven participatory processes to understand facility-level bottlenecks to optimise PMTCT implementation and to scale up priority PMTCT actions nationally. Results: There was remarkable improvement across all key indicators in the PMTCT cascade over the 3 years 2011 - 2013. Simple monitoring tools such as a visual dashboard and data for action reports were successfully used to improve the performance of the PMTCT programme across SA. MTCT has shown a significant downward trend. Conclusions: It is feasible to implement district-level, data-driven quality improvement processes at a national scale to improve the performance of the PMTCT programme at the local level.
PK
Keywords: HIV; HIV Infections